What's In It for Me? CEOs Whose Firms Are Acquired - Hartzell, Jay C.; Ofek, Eli; Yermack, David (Review of Financial Studies, 2004)
We study benefits received by target chief executive officers (CEOs) in completed mergers and acquisitions. Certain target CEOs negotiate large cash payments in the form of special bonuses or increased golden parachutes. These negotiated cash payments are positively associated with the CEO's prior excess compensation and negatively associated with the likelihood that the CEO becomes an executive of the acquiring company. Regression estimates suggest that target shareholders receive lower acquisition premia in transactions involving extraordinary personal treatment of the CEO. Target CEOs experience very high turnover rates both at the time of acquisition and, for those who remain employed, for several years thereafter.